The Impact of Social Media Marketing Activities and Customer Experience on Instagram on Outpatient Relationship Quality - Widasmara, Dhelya; Setijowati, Nanik; Rahmah, Shofi Nur (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Instagram, which ranks fourth globally in usage in Indonesia, has become an effective and cost-efficient marketing tool, especially in the healthcare sector. Hospitals, such as RSUD Dr. Saiful Anwar Malang, utilize Instagram to promote services and engage patients. However, despite a growing following and content, fluctuating patient visits suggest that the hospital's Instagram marketing strategy may need further optimization. The purpose of this study was to identify social media marketing activities (SMMA) and customer experience on Instagram regarding the relationship quality of outpatient patients at RSUD Dr. Saiful Anwar Malang. This study used a quantitative approach with a cross-sectional design and accidental sampling of outpatients during February-March 2024. Data were collected through surveys and analyzed statistically to examine the impact of SMMA and customer experience on Instagram on the relationship quality of outpatients.  The results of the multiple linear regression analysis show that SMMA has a significant effect on relationship quality (regression coefficient = 0.34, p=0.039), while customer experience has a significant positive effect (regression coefficient = 1.003, p=0.000), indicating that improving customer experience has a stronger impact on relationship quality compared to SMMA. The study concludes that SMMA has a partial effect on relationship quality, meaning that better SMMA increases relationship quality. This suggests that future media services should prioritize building connections, satisfaction, and patient retention.